Impact of Quran Therapy as a Complementary and Alternative Medicine in Cancer: Impact of Quran Therapy in Cancer - Khan, Imrana; Shareef, Huma (Pakistan Journal of Health Sciences, 2023)
Cancer patients suffer from the deleterious effects of the disease and its treatment. Quran Recitation therapy has been used as Complementary and Alternative Medicine (CAM) by Muslims for multiple diseases including cancer. Objective: To find the impact of Quran recitation therapy as CAM in the management of cancer. Methods: The study included full-text original research articles from a 10-year pooled data (2013 to 2023). The studies were divided into three categories i.e., cancer cell cultures, animal models and cancer patients. Results: Quran recitation on cancer cell cultures revealed an inhibition of cancer cell viability, proliferation and migration. Animal studies revealed increased T lymphocyte activity among the cancer cells and human studies revealed a significant reduction of anxiety, stress, depression, pain, nausea and vomiting during cancer management. Thus, the addition of Quran recitation therapy as a complementary medicine along with the standard medical treatment improved the prognosis and reduced the side effects of cancer treatment. Conclusions: Based on this evidence, Quran recitation can be used as a safe, non‑pharmacological treatment to improve the management of cancer.